Frontispiece: Intrinsically Disordered Tardigrade Proteins Self‐Assemble into Fibrous Gels in Response to Environmental Stress. Issue 1 (27th December 2021) - Malki, Anas; Teulon, Jean‐Marie; Camacho‐Zarco, Aldo R.; Chen, Shu‐wen W.; Adamski, Wiktor; Maurin, Damien; Salvi, Nicola; Pellequer, Jean‐Luc; Blackledge, Martin
Abstract : Proteins In their Communication (e202109961), Martin Blackledge et al. report the self‐assembly of intrinsically disordered tardigrade proteins into fibrous gels in response to environmental stress.